Hidrólise enzimática do óleo de amêndoas de tucumã na síntese de biodiesel etílico via processo hidrólise-esterificação - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
Astrocaryum aculeatum G. F. W. Meyer popularly known as tucumã (do Amazonas)is an Arecaceae species, an Amazon palm tree, which is considered an oilseed species with high potential for the production of biofuels. Biofuels have many advantages over fossil fuels such as the reduced toxicity and lower emission of greenhouse gases, due to the carbon cycling. This has stimulated its use and study so far. In large scale, is normally produced from vegetable oils or animal fats and methanol through the transesterification process by the homogenous alkalis catalysis. However this process is possible only to oils of fats with low contents of free fatty acids, which is not observed for most of oil sources available in the Amazon. This works aimed to study the production of biodiesel by an alternative process based on two-steps process of hydrolysis-esterification, with focus on the hydrolysis step performed by enzyme catalysis. Two lots of tucumã kernel oil were studied. The physicalchemical parameters from both lots were determined. Lot 01 has acid value of 55.06 mg NaOH/gand lot 02 11.09 mg NaOH/g. The fatty acid composition was determined by FAME (Fatty Acid Methyl Ester) conversion and GC-FID analysis and showed that tucumã oil has lauric, myristic and palmitic acid as major constituents. The use of lipases was initially studied by the determination of hydrolytic capacity of 11 different commercial lipases using tricaprylin as substrate. Considering the observed results and the costs of acquisition of each enzyme, two enzymes were selected for further studies, Candida rugosa (free enzyme) and Thermomyces lanuginosus (immobilized). The quantification of enzyme conversion of oil into free fatty acids was determined by two methods. The first, was developed in this work, and was based on TLC-densitometry and the other RP-HPLC was used to validate the results obtained by TLC-densitometry. This analytical method showed accuracy, precision and linearity to quantify the lipid conversion and was used to determine the enzyme activity in different experiments performed to determine the best catalytic conditions. The best conditions observed for de Candida rugosa lipase were 0.3 % of enzyme, 1 % of surfactant, phosphate buffer at pH 7.50, oil:buffer ratio of 1:1 (V:V), temperature of 40 ºC, stirring at 700 rpm for 10 hours. Then, the hydrolysis was performed in larger scale in a glass reactor and the products of both lots were converted into biodiesel by heterogeneous catalysis with ferric sulfate, in separate experiments using methanol and ethanol. Overall the best conversion was observed for the ethylic biodiesel, whose composition showed high purity that was confirmed by GC-MS analysis. The studied process based on enzymatic hydrolysis followed by esterification by heterogeneous catalysis showed very promising results that could, in theory,be applied in the conversion ofany oil source with high free fatty acid content, which is one of the most important challenges in the production of biodiesel.
Keywords: Astrocaryum aculeatum (Tucumã); Lipases; Hidrólise; Biodiesel; Combustíveis fósseis; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA